THE LOCALITY OF TAFSÎR AL-AZHÂR HAMKA: An Analitical Study of Surah Âli ‘Imrân Interpretation - Badruzaman, Abad; Aziz, Thoriqul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Recently, many tafsîr (interpretive) studies in Indonesia have been directed to the works of